Analysis of Teacher’ Digital Literacy Competencies as Support for Teachers’ Skills at SDN 7 Gunung Agung - Putra, Hagil Setiawan; Tohir, Ahmad; Mashari, Ali (STKIP Al Islam Tunas Bangsa dan HEPI, 2025)
Analysis of teachers' digital literacy competencies in elementary schools is an important factor in efforts to strengthen the quality of learning. This study aims to assess the extent to which teachers at SDN 7 Gunung Agung have digital literacy and the extent to which that literacy impacts the development of their abilities in digital teaching. The methodology used was quantitative with a cross-sectional survey design; all teachers at the school were the research population, and the sample was determined using total sampling techniques to ensure comprehensive representation. The research instrument was a standard questionnaire that measured three dimensions of digital literacy (technical, cognitive, social) plus a measurement of digital teaching skills covering the aspects of planning, implementation, and evaluation. Data analysis was performed using descriptive statistics to describe the profile of digital literacy and teaching skills, as well as linear regression (simple and hierarchical) to evaluate the relationship between digital literacy and teachers' digital teaching abilities. The findings show that most teachers have moderate to high levels of digital literacy, especially in the technical and social dimensions, while the cognitive dimension shows variation between individuals. The regression results prove that digital literacy contributes significantly to improving digital teaching skills (p < 0.05), with a coefficient of determination indicating that digital literacy explains a significant portion of the variance in teaching skills. The study concludes that strengthening teachers' digital literacy is a crucial strategy for supporting technology-based pedagogical skills. Practical recommendations include implementing structured and continuous digital literacy training so that teachers not only master technological devices but are also able to design, implement, and evaluate digital learning processes effectively.